2022
DOI: 10.21203/rs.3.rs-2314913/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of COVID-19 on Chinese overseas students' mental health: a multi-country cross-sectional analysis

Abstract: Background: COVID-19 caused serious mental health burden for international students. However, only several international students obtained related mental health services. The topic of international students' mental health has the bigger jump among social and educational concerns during the pandemic. This study surveyed the effects of COVID-19 on the mental health of Chinese overseas students to provide essential reference for identifying mental health problems of Chinese overseas students, so that they can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Various studies have shown that psychological distress, depression, and anxiety disorders negatively correlate with engagement in moderate physical activities [25]. Moreover, intense physical activity leads to even lower levels of academic stress, enhancing motivation and self-confidence among students [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown that psychological distress, depression, and anxiety disorders negatively correlate with engagement in moderate physical activities [25]. Moreover, intense physical activity leads to even lower levels of academic stress, enhancing motivation and self-confidence among students [26,27].…”
Section: Introductionmentioning
confidence: 99%